Ibadah Puasa Ramadhan dalam Perspektif Islam dan Kesehatan - Firdaus Firdaus; Tati Yalina Andiyah; Lidya Andita; Saras Ainurrochimah; Fajrul Hakim; Wismanto Wismanto (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Islam considers that health is part of Allah's greatest favor. Medically, fasting can cleanse toxins and substances that accumulate in the digestive tract, kidneys, and other organs of the body due to preservatives, dyes, artificial sweeteners, cancer-causing carcinogenic substances, cigarette smoke and others that accumulate over the years. Although our body's mechanisms have the ability to treat themselves, the body's capacity also has its limits. By fasting, the protection of the body's organs can be perfect. The purpose of this research is to inform Muslims that fasting is mandatory for us to carry it out. In the Qur'an, surah al-Baqarah 2:183. Allah SWT said, "O you who believe, it is obligatory to fast on you, it is obligatory to those before you, so that you may fear Allah". Fasting is one of the pillars of Islam that must be done by every Muslim who is mukalaf (who has reached puberty and has intellect) and who is not in hindrance (uzur). The type of research used is from various literature and the development of various references. The method used is analysis. The data of this study was obtained by collecting data related to the journal theme, then grouping, sorting, and deleting unnecessary data. Next is to present and conclude from various data collections. The results of this study are described systematically and concretely according to the order of focus that has been previously explained. The first step is to explain what fasting is. The second step is to quote all the sentences that describe the relationship between fasting and health according to leading experts.